Sugar recovery and optimization from bakery leftovers via subcritical water hydrolysis - Mohd Thani, Nurfatimah (2020)
Subcritical water hydrolysis is an emerging extraction technique that has been acknowledged as a green process. This study aims to recover sugar from leftover croissants (LC) (52.42 ± 0.29% of carbohydrate content) and leftover doughnuts (LD) (46.59 ± 0.23% of carbohydrate content) using subcritical water technique. The first part of this study determines the effect of process parameters (temperature, time and solid loading) of subcritical water hydrolysis (SWH) on sugar recovery. The sugar obtained from leftover samples (LC and LD) increased with an increase in temperature. Contrarily, increasing the solid loading decreased the total sugar yield. Enzymatic hydrolysis (EH), which considered as a conventional process, was also conducted to recover sugar with a different set of process parameters. SWH and EH were optimized using response surface methodology (RSM), where maximum sugar yield was the primary response. SWH recorded the optimised conditions at 200 °C, 6.17 min, and 10% solid loading that producing 466.11 ± 0.67 mg/g for LC, while for LD sample the optimised conditions were found at 200 °C, 5 min, and 10% solid loading with yielded of 394.34 ± 0.33 mg/g. EH recorded the optimum conditions of LC at 0.7% enzyme concentration, 49°C and pH 3 with a sugar yield of 574.21 mg/g, while for LD the optimum process condition was at 0.98% enzyme concentration, 47°C and pH 3 with sugar yield of 460.53 mg/g. The sugar recovered from the optimised process conditions was further characterized in terms of its morphology, chemical composition and its sugar degradation by-products. SEM revealed that starch granules of LC and LD appeared to be more ruptured in the SWH than EH. Meanwhile, FTIR detected the presence of monosaccharides and oligosaccharides from LC and LD hydrolysate. Hydroxymethylfurfural (HMF) was detected higher in SWH than EH. Kinetics of subcritical water hydrolysis were studied, and it was found that SWH was greatly dependent on temperature and time. The findings of this research can be beneficial to the food and pharmaceutical industries. This research can also benefit environmental and energy sustainability areas as it involved a green method in managing food waste issues worldwide.